Hermeneutics and the Humanities. Dialogues with Hans-Georg Gadamer - Kasten, Madeleine (Leiden University Press, 2012)
Hans-Georg Gadamer's "Wahrheit und Methode" (1960) is one of the most influential books on interpretation to have appeared in the past half century. This volume aims to continue this conversation between hermeneutics and the humanities, but also tries to map Gadamer's influence on the humanities so far.